Peran Masyarakat Dalam Pengembangan Pariwisata Kawah Upas Tangkuban Perahu (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
This research aims to analyze the role and participation of the community in the development of Upas Crater tourist destination in Tangkuban Perahu Mountain area, West Java. Methods This research uses qualitative with descriptive approach, data collected through field observations, in-depth interviews with community leaders, local community leaders, local tourism businesses, and visitors, as well as documentation studies. The results showed that the surrounding community plays an active role in various aspects of tourism development, including: 1. Provision of facilities and Provision of tourist facilities and services, 2. Preservation of the environment and local culture, 3. Management of tourist area security, and 4. Promotion of tourism through various social media. However, there are still some obstacles such as limited human resource skills, lack of business capital, and lack of coordination between stakeholders. This research recommends the need for capacity building the community through tourism training, strengthening local institutions, and optimizing cooperation between the community, government, and stakeholders. optimization of cooperation between the community, government, and private sector in the development of tourism destinations. development of a sustainable Upas Crater tourist destination.